Adjustment of preventive maintenance plans in CEMEX Colombia (2023)
It is important to mention that the effectiveness of preventive maintenance systems is difficult to evaluate. Also, it is wrong to state that one type of PM (Preventive Maintenance) is the best or the least desirable. The most common and generally accepted type of PM is periodic interval or calendar-based. However, this system has several weaknesses. To overcome some of these weaknesses, the usage-based system has certain advantages. Adopting this type of PM implies requirements for more accurate data collection and direct interaction with the process and plant equipment. It is necessary to judge whether the advantages of this type outweigh the possible difficulties of the industrial maintenance area of the company. Only a complete evaluation of the performance of both systems can answer this question. A practical evaluation of the two systems from an actual installation would be time-consuming and difficult to perform, the advantage in this case, however, is that the company has been using the schedule-based type, and what this project proposes is to start using the usage-based type to properly evaluate both options. The maintenance plans developed in this thesis provided the data to validly judge the advantages of one system over the other. The output data from the project projections showed significant differences in the equipment maintenance cost analyzed after a while in favor of the usage-based system. It was found that operating the equipment in both types of PM, the data showed up to 70% return on investment in maintenance when the equipment was subjected to usage-based PM. For a large operation, i.e., a nationwide project on most plant equipment, this represents significant economic savings and would justify the establishment of such a program.